ANALISIS SENYAWA BERBAHAYA PARFUM ISI ULANG YANG DIJUAL DI KOTA PADANG MENGGUNAKAN METODE KROMATROGRAFI GAS-SPEKTROMETRI MASSA - Asra, Ridho; Rusdi, R.; Arifin, Putut; Nessa, N. (Jurnal Riset Kimia, 2019)
Perfume is widely used by most of people in this world. The increasing demand of perfume has caused many producers cheating by adding dangerous compounds and also unregistered by the National Agency of Drug and Food Control Indonesia. The aim of this study is to analyze the dangerous compounds in unregistered perfumes sold in Pasar Raya Padang City by using gas chromatography-mass spectrometry (GC-MS) method. In this Study, samples (A, B, C, D and E) were collected and the value of specific weight and refractive index of the samples were analyzed. The results showed that five samples contained relatively similar chemical compounds. Twelve compounds were detected and seven of them were harmful to health in refill perfumes which were dipropylene glycol, linalool, lily aldehyde, benzenepentanol, dimethylbenzyl carbinyl acetate, dihydro methyl jasmonate, alpha hexyl cinnamic aldehyde, based on Material Safety Data Sheet (MSDS). Regular monitoring of chemicals used in the manufacture of perfumes which may cause health risks to users should be controlled by National Agency of Drug and Food Control Indonesia.